The Role of HR Strategy and Work Capability on Employee Performance of Bank Mandiri Palangka Raya Branch, Central Kalimantan-Indonesia - Ferdinand; Vivy Kristinae; Haipa Adila; Astrid (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine HR Strategy Analysis, Through Work Capability on Employee Performance of Bank Mandiri Palangka Raya Branch. This research method is this type of research is descriptive and quantitative. The results of the research are to provide solutions to phenomena in research problems, and at the same time link the formulation, benefits in the research hypothesis as causation with the SmartPLS 3.0 statistical analysis test. The type of sample data is primary data with a questionnaire of 35 people, employees at Bank Mandiri KCP Palangka Raya. The results of the research on HR strategy have a significant positive effect of 52.8% on performance, work ability has a significant positive effect of 38.1% on performance, the mediating role of work ability has a positive and significant effect of 25.9% on the relationship between HR strategy on performance.